2005
DOI: 10.1111/j.1471-6712.2005.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Achieving harmony with oneself: life with a chronic illness

Abstract: This paper presents partial findings of a larger research project focusing on what it means to live with a chronic illness. Getting in harmony with oneself is a movement towards, and a form of, acceptance of the chronic suffering and disease. Some patients achieve this level of acceptance, while for others the obstacles of everyday life make this movement towards acceptance difficult. Achieving harmony with oneself is conditioned by the existence of hope and spirit of life/life courage and by the pressure of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
0
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 9 publications
4
89
0
10
Order By: Relevance
“…The findings of our study showed positive experiences of equanimity; in other words, the participants were experiencing balance and harmony [20]. Harmony with oneself entails acceptance of chronic suffering and disease [37]. Experiencing harmony meant they accepted their life situation in accordance with Bury and Holmes [15], who found that older persons conduct their lives with equanimity.…”
Section: Discussionsupporting
confidence: 56%
“…The findings of our study showed positive experiences of equanimity; in other words, the participants were experiencing balance and harmony [20]. Harmony with oneself entails acceptance of chronic suffering and disease [37]. Experiencing harmony meant they accepted their life situation in accordance with Bury and Holmes [15], who found that older persons conduct their lives with equanimity.…”
Section: Discussionsupporting
confidence: 56%
“…Casi de un modo inevitable la persona se da cuenta que existe una naturaleza más allá de los límites físicos e individuales. Esta experiencia, referida por diversos autores desde el ámbito espiritual, facilita el punto de inflexión por el que la persona integra y da sentido a la experiencia de FV (16,18,(20)(21)(22)29,33) . Detectar fuentes de sentido en la experiencia de EA al FV conlleva un trabajo de fondo en relación con la motivación existencial.…”
Section: Discusión/conclusionesunclassified
“…Palabras escritas ya hace quince años pero que siguen siendo un reto y un horizonte en el momento presente. Desde esta perspectiva diversos autores han subrayado determinadas dimensiones que han tenido un impacto en el modo en que se da respuesta al sufrimiento al FV (8,12,13,20,21) . Estos autores han puesto el énfasis para afrontar el sufrimiento en las conexiones sanadoras desde una experiencia de integridad, plenitud y trascendencia (20) , en el proceso de reconciliación (22) , en lograr armonía con uno mismo (21) , en los procesos de encontrar sentido a la experiencia de EA (12,13,23) y en la naturaleza de la esperanza y la compasión durante la enfermedad crónica avanzada (24) .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Cechy osobowości są szczególnie ważne w procesie radzenia sobie i przystosowania do choroby przewlekłej. Do najistotniejszych cech należą: umiejętność radzenia sobie w sytuacjach trudnych, typ reagowania emocjonalnego, zdolności, nadzieja, optymizm, wiara w sukces, aktywność życiowa, obraz siebie i samoocena [5,6]. Układ cech osobowości może predysponować jednostkę do rozwoju zaburzeń psychicznych, a także nasilenia dolegliwości somatycznych.…”
Section: Wstępunclassified